Biodiversity of subterranean termites on the Acacia crassicarpa plantation - NOOR FARIKHAH HANEDA; ICHMA YELDHA RETMADHONA; DODI NANDIKA; ARINANA ARINANA (Biodiversitas Journal of Biological Diversity, 2017)
Haneda NF, Retmadhona IY, Nandika D, Arinana. 2017. Biodiversity of subterranean termites on the Acacia crassicarpa plantation. Biodiversitas 18: 1657-1662. The development of industrial plantation forests is one of the efforts to meet the needs of raw material of processing industry of timber forest products. In the last 15 years, the development of industrial plantation forest has grown rapidly. Plant species widely developed is fast-growing plants (fast growing trees) such as Acacia crassicarpa Cunn ex Benth. However, A. crassicarpa has a low resistance against pests, evidenced by the presence of subterranean termites attack occurred in the industrial plantation forest of A. crassicarpa. This aim of the study is to determine the diversity of subterranean termites in plantation forest of A. crassicarpa. Two methods used for data collection: baiting system and survey. Five species of subterranean termites found on sample paths were Coptotermes curvignathus Holmgren, C. gestroi Wasmann, Schedorhinotermes javanicus Kemner, Longipeditermes longipes Haviland, and Pericapritermes mohri Kemner. These species can be distinguished from the morphology of the mandible. Coptotermes is most commonly found Genus in study plots.